Extra-abdominal and intra-abdominal FET::CREM fusion mesenchymal neoplasms: comparative clinicopathological study of 9 new cases further supporting a distinct potentially aggressive sarcoma and report of novel sites - Agaimy, Abbas; Blakely, Morgan; Breimer, Gerben E.; Hölsken, Annett; Koppes, Sjors A.; Meidenbauer, Norbert; Rijken, Johannes A.; Schad, Arno; Simon, Adrian G.; Stöhr, Robert; Bishop, Justin A.; Din, Nasir Ud (Virchows Archiv, 2024)
With the wide use of RNA sequencing technologies, the family of FET::CREB fusion mesenchymal neoplasms has expanded rapidly to include potentially aggressive neoplasms, not fitting any well established WHO entity. Recently, a group of intra-abdominal FET(EWSR1/FUS)::CREB(CREM/ATF1) fused unclassified neoplasms has been reported followed by recent recognition of an analogous extra-abdominal category of unclassified neoplasms carrying EWSR1::ATF1 fusions. We describe 9 additional tumors (5 extra-abdominal and 4 abdominal) carrying an EWSR1::CREM (n = 8) and FUS::CREM (n = 1) fusion. Patients were 7 females and 2 males aged 10 to 75 years (median, 34). Extra-abdominal tumors originated in the head and neck (2 sinonasal, 1 orbital) and soft tissues (1 gluteal, 1 inguinal). Abdominal tumors involved stomach (2), mesentery (1), and kidney (1). Tumor size ranged from 3.5 to 11 cm (median, 6). Treatment was radical surgery with (5) or without (2) neo/adjuvant radio/chemotherapy. Extended follow-up of 5 patients (21–52 months; median, 24) showed an aggressive course in two (40%); one died of disseminated metastases 52 months after several intensified chemotherapy regimens, and one was alive with progressive abdominal disease at 21 months. The immunophenotype of the two subcohorts was significantly overlapping with variable expression of EMA (7 of 8), keratin AE1/AE3 (5 of 9), CD99 (4 of 7), MUC4 (2 of 8), ALK (3 of 8), synaptophysin (3 of 9), chromogranin (1 of 8), CD34 (3 of 6), CD30 (1 of 6), PAX8 (1 of 7), and inhibin (1 of 7), but no reactivity with desmin (0 of 8), S100 (0 of 8), and SOX10 (0 of 8). This series further solidifies the notion that FET::CREB fusions are not limited to the triad of angiomatoid fibrous histiocytoma, clear cell sarcoma, and malignant gastrointestinal neuroectodermal tumor, but characterize an emerging family of potentially aggressive neoplasms occurring at both intra- and extra-abdominal sites. These tumors underscore the promiscuity of the FET::CREB fusions and highlight the pivotal role of phenotype-oriented classification of these neoplasms that share the same genotype, still featuring significant biological and behavioral distinctness.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Constitutional symptoms; Ewing sarcoma; Genetic landscape; Next generation sequencing; Precision medicine; Profiling